Infections among adults hospitalized in intensive care after the 2023 earthquake in the southeastern part of Türkiye: a multi-center observational study - Esat Kivanc Kaya; Burcin Halacli; Goksel Guven; Mehmet Yildirim; Asir Eren Seven; Emin Gemcioglu; Meltem Simsek; Begum Erdemir Sullu; Recep Civan Yuksel; Ahmet Safa Kaynar; Aliye Esmaoglu; Banu Kilicaslan; et al. (BMC Infectious Diseases, 2025)
Abstract Background Scarce evidence is available on the epidemiology of microbiologically proven clinical infections in patients admitted to the intensive care unit (ICU) after a great earthquake. The main aim of this study was to assess clinical infections and microbiological features in patients admitted to the ICU following the 2023 earthquake in the southeastern region of Türkiye with a focus on the timing of culture positivity during their ICU stay. The secondary objectives included determining antibiotic susceptibility patterns, identifying the types of antibiotics administered upon ICU admission, evaluating the appropriateness of antibiotic usage, assessing patient outcomes, and identifying factors that influence microbiologically confirmed clinical infections. Methods A retrospective, multicenter, observational study was conducted on adult earthquake victims admitted to the ICU after the 2023 earthquake in southeastern Türkiye. Patients were categorized into four groups on the basis of culture positivity timing at the 72-hour breakpoint and clinical characteristics were compared among these groups. Factors influencing microbiologically proven clinical infections were also analysed. Results A total of 107 earthquake-affected adults (58 females and 49 males, median [IQR] age: 37 [27–57] years) were analysed. Infection was present in 50.5% of the patients, predominantly with multidrug-resistant pathogens. Amputation (OR 5.30) and intermittent hemodialysis (OR 2.98) before ICU admission were independent predictors of infection. Conclusions This study demonstrated that half of the patients admitted to the ICU with earthquake-related injuries had microbiologically proven clinical infections, highlighting the early presence of multidrug-resistant pathogens.